Cash crops as a sustainable pathway out of poverty? Panel data evidence on the heterogeneity of cocoa farmers in Sulawesi, Indonesia - Elisabeth Hettig; Jann Lay; Katharina van Treeck; Martin Bruness; Dewi Nur Asih; Nunung Nuryartono (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
The cultivation of cash crops has a great potential for reducing poverty in the developing world that may not be fully harnessed because many smallholders are inefficient producers. Further, income gains may be only static and poverty and vulnerability of smallholder households may not be reduced sustainably. Instead, cash crop farmers, in particular those without proper farm management skills, may experience boom and bust cycles, caused by volatile world market prices local weather shocks and pests. To analyze the long-term poverty impacts of cash crop agriculture, we draw on a unique panel data set of smallholder cocoa farmers in Central Sulawesi, Indonesia, covering the years 2000, 2006 and 2013. We show that - over the analyzed time horizon of more than 10 years - cocoa cultivation is associated with strong and sustainable poverty reduction. Cocoa farmers fare better than non-cocoa farmers and the welfare gains can mainly be attributed to increasing cocoa yields. Yet, yield gaps remain large and are increasingly heterogeneous. We can trace back this productivity heterogeneity to farm management practices. Linking these findings to poverty transitions, we can show that better management practices facilitate the transition out of poverty and shields against income losses.
Keywords: 330